O CLUBE DA LEITURA NA BIBLIOTECA ESCOLAR: a construção de novos sentidos, em situação de leitura compartilhada, por crianças em processo de alfabetização. - PINTO, Michelle Silva (2019)
This master's dissertation aimed to understand the ways in which children in the process of literacy appropriate the act of reading, in situations of readings mediated by discursive sessions of a Reading Club in the school library. The locus of this study comes from readings mediated by discursive sessions of a Reading Club. Its specific objectives were: a) To identify children's reading practices in the school environment and how they relate to the writings available at school. b) Understand the theoretical-methodological conceptions that guide the action of the teacher-literate in the teaching of reading and the use of the school library, as cultural practices. c) Analyze the different ways in which literate children assign meanings in order to understand how they redefine these meanings by being exposed to new spaces of elaboration through the sharing of readings in a Reading Club. d) Produce a book with the reflections developed during the course of creating a Reading Club. This is an action research, pedagogical intervention type. Its theoretical basis is the methodological principles of the philosophy of language, in particular those highlighted by Bakhtin and Volóchinov. The field research was carried out in a public school of the São Luís-MA Municipal Education Network, through “Dialogues Meetings” between the researcher and the research collaborators - students and teachers of two classes of the 3rd year of Elementary School. . Data were recorded in Field Diary, audios and recorded videos, always preserving the complete dialogues, to respect the integrity of the orality of their authors. It was adopted as a central reference the theoretical assumptions of studies by Volóchinov (2017) and Bakhtin (2016), which moved the researcher's thinking about language and its possible implications for the teaching of reading as a cultural practice. To this end, the readings were subsidized, with the studies of contemporary authors dealing with this theme, such as Arena (2003; 2008, 2011), Bajard (2002), Correia (2011), Lerner (2002), Jolibert (1994; 2006) and Mortatti (2006, 2012 and 2014) and others, who, among other activities, helped to analyze the data. The data were organized in the following thematic nuclei: The school library as a cultural center where it is also possible to appropriate languages and the cultural act to read writings and the Reading Club and the literary text as spaces for the elaboration of new meanings, in the meeting of the reader with the written text, in situations of readings shared with Others. It is considered possible to produce a methodological strategy for the teaching of reading, using the dynamics of a Reading Club, in order to analyze the ways in which children in the process of literacy attribute meanings to what they read, and subsequently share in a conversation wheel. Thus, these meanings are re-signified by having contact with the meanings attributed by the Other (s), derived from the life circumstances of each reader. The intervention work carried out at / by the school library brought significant changes in the human development process of the students, who moved from beginner gestures and operations on reading, to more elaborate and / or erudite reading attitudes, as is the case with practice. to read in a group at a Reading Club.